Performance of acute flaccid paralysis surveillance compared with World Health Organization standards. (30th July 2014) - Desai, Shalini; Smith, Tiffany; Thorley, Bruce R; Grenier, Danielle; Dickson, Nigel; Altpeter, Ekkehardt; SPSU Committee; Sabbe, Martine; Elliott, Elizabeth; Zurynski, Yvonne
<x xml:space="preserve">Abstract</x> Aim To compare acute flaccid paralysis (AFP) surveillance systems used by members of the International Network of Paediatric Surveillance Units (INoPSU) across the five AFP surveillance performance indicators recommended by the World Health Organization (WHO) for the maintenance of polio‐free certification. Methods A survey was administered to AFP surveillance co‐ordinators in five INoPSU member countries (Australia, Belgium, Canada, New Zealand and Switzerland). Data collected included information on surveillance system processes, WHO‐recommended performance indicators, investigative practices and final diagnoses of cases from 2006 to 2010. Results All countries contacted completed the survey. Each country used similar case definitions and processes for collecting AFP data. All countries used at least one of the WHO indicators for surveillance. No country consistently met the performance indicator for incidence or stool sampling. In all countries, at least one form of neurological testing was used to diagnose cases of AFP. Guillain‐Barré syndrome was the most common final diagnosis in all countries for all years examined. Conclusions Industrialised countries surveyed do not consistently meet the WHO‐recommended AFP surveillance performance indicators. An opportunity exists for INoPSU to suggest a standard way for member countries to collect AFP data in order to examine the potential for strengthening the current systems or introducing additional enterovirus surveillance or alternative/complementary neurological performance measures suitable for countries that have eliminated polio. INoPSU member countries are evaluating these possibilities.